2011
DOI: 10.1007/s11207-010-9696-z
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Spectroscopy of a White-Light Solar Flare

Abstract: We report observations of a white-light solar flare (SOL2010-06-12T00:57, M2.0) observed by the Helioseismic Magnetic Imager (HMI) on the Solar Dynamics Observatory (SDO) and the Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI). The HMI data give us the first space-based high-resolution imaging spectroscopy of a whitelight flare, including continuum, Doppler, and magnetic signatures for the photospheric Fe I line at 6173.34 Å and its neighboring continuum. In the impulsive phase of the flare, a br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 30 publications
(38 reference statements)
2
32
0
Order By: Relevance
“…The acceleration of electrons outward to relativistic speeds generating radio emission is linked to the hard X-ray emission from the inward-penetrating electrons. Investigations of white light flares in spectral lines and continuum bands with multiple satellites demonstrate their temporal and spatial coherence with hard X-ray emission (Martínez Oliveros et al 2011;Watanabe et al 2013). This supports the case of white light emission occurring primarily during the IP.…”
Section: Introductionsupporting
confidence: 59%
“…The acceleration of electrons outward to relativistic speeds generating radio emission is linked to the hard X-ray emission from the inward-penetrating electrons. Investigations of white light flares in spectral lines and continuum bands with multiple satellites demonstrate their temporal and spatial coherence with hard X-ray emission (Martínez Oliveros et al 2011;Watanabe et al 2013). This supports the case of white light emission occurring primarily during the IP.…”
Section: Introductionsupporting
confidence: 59%
“…In the case discussed by Martínez Oliveros et al [], HMI data showed spurious blue shifts of the Fe line. In addition, temporal interpolation involving negative coefficients in adjacent 45 s intervals can result in spurious “black‐light” flares [ Martínez Oliveros et al , ]. These factors complicate the interpretation of the HMI white‐light continuum images and presumably introduce a large uncertainty in the corresponding white‐light fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…For a given wavelength/polarization pair, the temporal interpolation ordinarily requires six Level-1 filtergrams in definitive mode and two in NRT mode to interpolate to the requested time. The two-point NRT temporal interpolation is a basic linear scheme, while the definitive six-point method uses the specific weighting scheme described in Martínez Oliveros et al (2011). When the loop over all wavelengths and polarizations is complete, the result is a set of filtergrams with the same solar radius and Sun-center position all interpolated to the proper observable time: T_OBS at the spacecraft.…”
Section: Filtergram Selection Mapping and Image Processingmentioning
confidence: 99%